2008
DOI: 10.1111/j.1745-459x.2008.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Paired Preference Tests: “50:50” and “Alternating” No Preferences

Abstract: Because the concept of “No Preference” is ambiguous, two types of “No Preference” are defined: a “50:50” No Preference, defined operationally as consumers presented with both products having a 50% chance of choosing either, and an “Alternating” No Preference, where the probability is not 50%. The consumer would be more likely to choose one of the products. However, later, he or she might choose the other product. To investigate this, paired preference tests were performed with and without the “No Preference” o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The second approach for utilizing chi‐squared is simpler and accordingly has been applied by various authors (Alfaro‐Rodriguez et al . 2007, 2008; Kim et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second approach for utilizing chi‐squared is simpler and accordingly has been applied by various authors (Alfaro‐Rodriguez et al . 2007, 2008; Kim et al .…”
Section: Methodsmentioning
confidence: 99%
“…2003; Chapman and Lawless 2005; Chapman et al . 2006; Alfaro‐Rodriguez et al . 2007, 2008; Kim et al .…”
Section: Introductionmentioning
confidence: 99%
“…The “No Preference” frequencies vary but are mostly in the range 20% to 30%. (Marchisano and others ; Chapman and Lawless ; Chapman and others ; Alfaro‐Rodriguez and others , , ; Kim and others ; Angulo and others ; Alvarez‐Coureaux and others ). Consequently, rather than using a “one‐size‐fits‐all” identicality norm, it was considered appropriate for a sample of consumers to generate their own identicality norms, according to the appropriate experimental conditions, the products being tested and the types of consumers making the assessments.…”
Section: Introductionmentioning
confidence: 95%
“…Ennis and Collins's () 40‐20‐40 frequency distribution for putatively identical stimuli does not seem to be general. For reasons as yet unresolved, other authors (Alfaro‐Rodriguez, Angulo, & O'Mahony, ; Alfaro‐Rodríguez, O'Mahony, & Angulo, ; Alvarez‐Coureaux, Aguilar, O'Mahony, & Angulo, ; Angulo, Okayama, Nakamura, Yuen, & O'Mahony, ; Calderón et al, ; Chapman, Grace‐Martin, & Lawless, ; Chapman & Lawless, ; Sung et al, ; Kim, Lee, O'Mahony, & Kim, ; Marchisano et al, ; Xia et al, ) found different frequencies, the numbers varying with the products being tested, the experimental conditions, the types of consumers tested and the types and numbers of response options available in the test. The frequencies of reported “No Preferences” vary a great deal but most are in the range 20–35%.…”
Section: Introductionmentioning
confidence: 99%
“…The safest approach at the present time, would appear to be to require consumers to assess the target (different) pair and also the putatively identical (placebo) pair to give a measure of the effect of the extraneous factors. This was adopted and involved giving consumers two pairs to assess in a given test (Alfaro‐Rodriguez et al, ; Alvarez‐Coureaux et al, ; Kim et al, ; Sung et al, ). Using Chi‐squared, the responses elicited by the target pair of (different) stimuli were not compared with the null hypothesis but were instead compared with the hypothesized identicality norm, derived from the putatively identical pair, to see whether they were significantly different.…”
Section: Introductionmentioning
confidence: 99%